2015
DOI: 10.1186/s40798-015-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized personalized music audio-playlists to improve adherence to physical activity among patients participating in a structured exercise program: a proof-of-principle feasibility study

Abstract: BackgroundPreference-based tempo-pace synchronized music has been shown to reduce perceived physical activity exertion and improve exercise performance. The extent to which such strategies can improve adherence to physical activity remains unknown. The objective of the study is to explore the feasibility and efficacy of tempo-pace synchronized preference-based music audio-playlists on adherence to physical activity among cardiovascular disease patients participating in a cardiac rehabilitation.MethodsThirty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 55 publications
1
71
0
Order By: Relevance
“…In our study, since we had selected music preferred by the participants, added to the fact that the subject was in a relaxed mood must have accounted for the music induced alterations in sympathetic and parasympathetic activity during exercise. Our findings are in agreement with the recent works [37,38]. It is clear from our results that preferred music has a definite calming effect on exercise induced changes in HRV which is in accordance with the work of Pal et al, who have shown that practice of relaxation therapy with soothing music in the background was effective in lowering the LF/HF ratio of HRV in medical students [39].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, since we had selected music preferred by the participants, added to the fact that the subject was in a relaxed mood must have accounted for the music induced alterations in sympathetic and parasympathetic activity during exercise. Our findings are in agreement with the recent works [37,38]. It is clear from our results that preferred music has a definite calming effect on exercise induced changes in HRV which is in accordance with the work of Pal et al, who have shown that practice of relaxation therapy with soothing music in the background was effective in lowering the LF/HF ratio of HRV in medical students [39].…”
Section: Discussionsupporting
confidence: 93%
“…The tempo of running, or cadence, refers to the frequency of steps, whereas speed (expressed in km/h) refers to the total distance travelled in a certain amount of time. In previous studies, the preferred exercise intensity was often measured before the actual experiment and the music tempo was generally rather coarsely matched to a subject's spontaneous or comfort tempo (e.g., within a 10% range of the assessed cadence) [13, 14]. However, such an approach disregards the fact that the comfort tempo of an individual might be different at the time of the test, or that it might fluctuate during the test period.…”
Section: Introductionmentioning
confidence: 99%
“…If globalization is really destroying cultural identities and transforming them into a more market-oriented and collective one, it seems reasonable to assume that cultural products such as films and music would be more homogeneous, universal, and commercialized than they were in the past. This anxiety over losing local culture and individual traditions in cultural production is particularly evident in the music industry, especially when digital technologies like voice synthesis are gradually replacing traditional music materials, including conventional ethnic instruments and performances (Alter et al, 2015). However, a small number of researchers have continued to pursue a line of inquiry associated with the critics of cultural imperialism, claiming that the application of technologies has made forms and styles of culture creep toward hybridization rather than homogeneity (Born & Hesmondhalgh, 2000).…”
Section: Cultural Identity: a Product Of Globalizationmentioning
confidence: 99%